(3CfhGQ GdabGgIs - (3GdLfGMj, GdfLaj, cGTa GdZWGA, MSf Hf LYaQ Hf NVQ, J (B1262 (3g`s
(3ChdgG (B:s
... (3cJGH GdUjGe hgh ef VQhQjGJ GdESdGe hhLHg aj TgQ QeVGf fWb Hg GdbQBf hUGQ VQhQjG aj LejY GdGReGf hGdUhe dZI GdEeSGc Yf GdTjA hfbd TQYG aj Ref GdTGQY HfGA Ydi KHhJ GdMbjbI GdTQYjI (B...s
(3BNQgG (B:s
... (3def hWF RhLJg ecQgG aj GdGYJcGa aj TgQ QeVGf YOe hLhH JMed GdcaGQI aj ZjQ eG Od Ydjg GdOdjd hbO GNJU ehQOg HUjGe TgQ QeVGf adG jJYOi dcd eG jhLH GdcaGQI dCfg bjGS (B. (3Je cJGH GdUjGe hGdGYJcGas
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1\543s
(3GdPQjYI (B2 - 244( 1702)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis